Estudio de los factores de comercialización de la mora en la comunidad tambo real parroquia Guanujo cantón Guaranda provincia Bolívar año 2016 - Punina Ortiz, Shirley Karina (2016)
This work previous to get the degree in bussiness engineering that is named “process in the fail of the bussiness at Tambo Loma community, Guanujo town, Bolivar province, 2016 year. done the analized about the fail in the debt and for sale of the third people. this produces that product was, is, and will be cheaper than other products the people usually sell. it is appropriate to explain that all Tambo Real area is dedicated to the production of default of castile, which is a good quality product: sweet, juicy flavor and aroma; because it occurs at the top of the range, boundaries between the mountains and subtropics, where humidity is permanent and the land is suitable for cultivation. the problem is that producers take the arrears to the main road and sell at very low prices to guarandeños and ambateños intermediaries that go to the place to buy the product and then move to the markets of their cities to be resold to a higher price. products made from mulberry are sold in restaurants, markets, malls, supermarkets and shops, whose value leave good profits to those engaged in this activity. in this research, scientists, inductive and deductive methods are utilitarian. in order to give a solution we analyzed all problems such as: distance sowing, transplanting, crop diseases, planning crop, facilities, tools, soil management, propagation material, plant nutrition , crop protection, harvesting and handling and postharvest, environmental protection, sales strategy, pricing strategy, finding new customers, customer retention, customer service, pruning, harvesting, duration of the vegetative cycle, quality standards, standards packaging, transportation.